Reshifting Power: From Democracy to Juristocracy? - Ehs, Tamara (Momentum Quarterly, 2012)
Regarding the principle of separation of powers, the judiciary had originally held the weakest part. Today, however, we can observe a significant shift of power from representative to judicial institutions. Therefore, some scholars already speak of a juristocracy. Against this background the paper discusses – especially constitutional – jurisdiction in terms of the power issue. The centerpiece of this analysis is a discussion of supreme courts as often insufficiently legitimated in terms of democracy, yet very powerful political players. Constitutionalisation and internationalisation have increased the importance of supreme courts as governing bodies. This not only has implications concerning legal action upon the policy, but just as much concerning the political bases of jurisdiction. Case studies of selected European countries and of the ECJ highlight the potential for conflict of judiciary towards the legislature. The study is based on the criticism of New Constitutionalism, follows the Political Jurisprudence movement concerning its analysis and tries to explain the power shift with Ran Hirschl’s theory of hegemonic preservation.